Incidence of Tooth Loss in Adults: A 4-Year Population-Based Prospective Cohort Study - Silva-Junior, Manoelito Ferreira (Int J Dent, 2017)
OBJECTIVE: To verify the incidence of tooth loss in extended age group of adults in 4 years. MATERIALS AND METHODS: The prospective cohort study assessed adults (20–64 years old) between 2011 and 2015, from Piracicaba, São Paulo, Brazil. The dependent variable was cumulative incidence of tooth loss, assessed by difference between missing teeth (M) of decayed, missing, and filled tooth index (DMFT) in 2011 and 2015. Participants were stratified into young (20–44 years old) and older (45–64 years old) adults. Mann–Whitney U test (p < 0.05) was used to compare the means of incidence of tooth loss between age groups. RESULTS: After four years, 57.7% (n = 143) of adults were followed up and the mean incidence of tooth loss was 0.91 (SD = 1.65); among these, 51 adults (35.7%) who lost their teeth showed mean tooth loss of 2.55 (SD = 1.86). In older adults, incidence of tooth loss was higher (p = 0.008), but no difference between age groups was found when only adults with incidence of tooth loss were assessed (p = 0.844). CONCLUSION: There was higher incidence of tooth loss in older adults after four years, however, without difference between age groups when only those who lost teeth were evaluated.